Role of atrial natriuretic peptide in the dissociation between flow relations with ventricular mass and function in a community with volume-dependent hypertension - Yusuf, Suraj M.; Norton, Gavin R.; Peterson, Vernice R.; Mthembu, Nonhlanhla; Libhaber, Carlos D.; Tade, Grace; Bello, Hamza; Bamaiyi, Adamu J.; Mmopi, Keneilwe N.; Dessein, Patrick H.; Peters, Ferande; Sareli, Pinhas; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Whether differential effects of volume load on left ventricular mass (LVM) and function occur in sustained volume-dependent primary hypertension, and the impact of atrial natriuretic peptide (ANP) on these effects, is unknown. Methods From aortic pressure, velocity and diameter measurements and echocardiography, we determined in an African community (n = 772), the impact of systemic flow-induced increases in central pulse pressure (PPc) and circulating ANP (ELISA) on LVM and indexes of function. Results Stroke volume (SV), but not aortic flow (Q), was associated with LVM and mean wall thickness (MWT) beyond stroke work and confounders (p < 0.0001). Adjustments for SV markedly decreased the relationships between PPc and LVMI or MWT. However, neither SV, nor Q were independently associated with either myocardial s', e', or E/e' (p > 0.14) and adjustments for neither SV nor Q modified relationships between PPc and s', e' or E/e' (p < 0.005 to <0.0001). SV was nevertheless strongly and independently associated with ANP (p < 0.0001) and ANP was similarly strikingly associated with s' (p < 0.0001) and e' (p < 0.0005), but not E/e', independent of confounders and several determinants of afterload. Importantly, ANP concentrations were inversely rather than positively associated with LV diastolic dysfunction (DD) (p < 0.005) and lower rather than higher ANP concentrations contributed markedly to the ability to detect DD in those with, but not without LV hypertrophy. Conclusion In populations with sustained volume-dependent hypertension, flow (SV)-related increases in PP have a major impact on LV structure, but not on function, an effect attributed to parallel striking beneficial actions of ANP on myocardial function.